THE FUTURE THROUGH DIGITAL TECHNOLOGY ENGINEERS PROFESSIONAL PREPARATION IMPROVING DEVELOPMENT METHODOLOGY (American Journal of Pedagogical and Educational Research, 2026)
This article aims to identify priority areas for the development of the educational process, based on the use of digital technologies in the higher education system of our republic, their potential, and the forms in which they are implemented.